Análisis del sistema de control interno en la empresa Brunner SAC de la ciudad de Iquitos, periodo 2021 - Guerra Rengifo, Rosa Sidy (2022)
The internal control system is a management tool and of vital importance for any organization, as it constitutes a set of actions, standards, techniques, development of procedures, preparation of plans and methods aimed at timely preventing the existence of risks that could affect the entity´s results. The present investigation entitled “Analysis of the Internal Control System in the company Brunner SAC of the city of Iquitos, period 2021”, had as general objective to determine the level of the internal control system in the company Brunner SAC of the city of Iquitos, period 2021. Likewise, the research was of a quantitative type and of a descriptive non-experimental-cross-sectional design. From the analysis and discussion of the result obtained, it was possible to determine that Brunner SAC company in the city of Iquitos for the study period presents a low level in its internal control system.